Copper-Catalyzed Protoarylation of gem-Difluoroallenes - Li, Wei; Wang, Cheng; Xiao, Mengdie; Cheng, Li-Jie (Organic letters, 2024)
A copper-catalyzed protoarylation of gem-difluoroallenes with aryl boronic esters has been developed, enabling highly regioselective synthesis of gem-difluoroalkenes in high yields. The mild reaction conditions allow for a variety of functional groups to be tolerated, and the reaction can be extended to protoalkenylation of gem-difluoroallenes. The synthetic utility of this method has been demonstrated in gram-scale operation as well as synthesis of chiral gem-difluoroalkenes bearing γ-carbon stereogenic centers in moderate enantioselectivity using a chiral bidentate phosphine ligand with a copper catalyst.